Market Competition in Blaru Village’s Cashew Industry, Kediri Regency: Structure–Conduct–Performance Analysis - Atunnisa, Tsania Mir; Satriawan, Bondan (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
This study analyzes the market structure, firm conduct, and market performance of small and medium-sized cashew-processing industries in Blaru Village, Badas District, Kediri Regency, using the Structure–Conduct–Performance (SCP) framework. A descriptive mixed-methods approach combining quantitative and qualitative analysis was employed. The study initially sought to include the entire population of 17 cashew-processing enterprises; however, three business operators declined to participate, resulting in a final sample of 14 respondents, comprising seven Level 1 producers and seven Level 2 producers. Market structure was analyzed using market share, the Four-Firm Concentration Ratio (CR4), the Herfindahl–Hirschman Index (HHI), and barriers to entry. Firm conduct was examined through pricing strategies, product differentiation, advertising and promotion, potential cooperation, and other competitive practices, while market performance was assessed using P–AC deviation, the Capital–Labor Ratio (CLR), and the Price–Cost Margin (PCM). The results indicate an oligopolistic market structure, with CR4 values of 81.60% for Level 1 producers and 95.54% for Level 2 producers. Entry barriers include limited access to capital and business legality constraints. Firm conduct is characterized by market-following pricing, limited differentiation and promotion, and the absence of formal collusion. Market performance reflects imperfect competition, with relatively high profit margins among some business operators. Overall, the industry exhibits high market concentration and limited competitive intensity. Keywords: Structure–Conduct–Performance; Market Concentration; Cashew-Processing Industry; Small and Medium-Sized Industries (SMIs); Kediri Regency; Indonesia.